Detection of BlaIMP and BlaOXA-23-LIKE Genes in Acinetobacter Baumannii Isolates at Dr. Wahidin Sudirohusodo Hospital (Indian Journal of Public Health Research & Development, 2020)
Background/Objective: Carbapenem resistant Acinetobacter baumannii (CRAB) is an A. baumannii resistant to one or more carbapenem antimicrobials. Some of resistance mechanisms that can be foundin CRAB are carbapenemase production, outer membran protein (OMP) or penicillin binding proteins(PBP) structure modification, or efflux pump increase. Carbapenemase production can be affected bycarbapenemase-encoding genes such as blaIMP and blaOXA23-like gene. This study aimed to detect the blaIMPand blaOXA23-like gene in A. baumannii isolates.Material and Method : It was observational descriptive study with cross sectional approach. Subject ofthis study were all A. baumannii isolates collected during the period of October 2018 until January 2019 atDr. Wahidin Sudirohusodo Hospital, Makassar, South Sulawesi, Indonesia (consisted of 30 CRAB and 20sensitive carbapenem A. baumannii (CSAB) isolates). Isolates were examined by polymerase chain reaction(PCR) and agar electrophoresis techniques.Results : There were 5 CRAB isolates with blaIMP gene and 23 isolates with blaOXA23-like gene. There wereno CSAB isolates with blaIMP gene and 2 isolates with blaOXA23-like gene.Conclusion : Carbapenemase-encoding genes could be found in CRABs and CSABs. In this study, blaOXA23-like gene was found in both CSAB and CRAB isolates but blaIMP gene was only found in CRAB isolates.
Keywords: Acinetobacter baumannii, carbapenem resistant, carbapenem sensitive, blaIMP, blaOXA-23-like